METODE PEMECAHAN MASALAH MODEL SSCS (SEARCH, SOLVE, CREATE, AND SHARE) DALAM PEMBELAJARAN MATEMATIKA - R a h m i, R a h m i (Prodi Pendidikan Matematika, 2013)
One of the innovations in learning mathematics than can fulfill the demands at this time is problem solving method model SSCS (Search, Solve, Create, and Share). In using this method, the students are included directly in finding the concept, in order to make their learning process more valuable. Besides that, they also can be more active because they are trained to formulate a problem, design solution, formulate the result and also communicate the results that they get.There are four phases in learning method model SSCS, that are 1) the Search phase is a phase related to ideas to make problem identification easier, 2) the Solve phase which centred at specific problem that have determined at the searching phase and the students are required to have the result and declared their planning in getting an answer, 3) the create phase that required the students to have answers to the problems that doing generalization, and even doing modification if needed, and 4) the share phase, the basic concept of the share phase is including the students in communicating the answers through the problems or question and answer, and then reproduce the questions to be investigated in another activity.